Explanation of the European Lepidocyrtus pallidus–serbicus group (Collembola, Entomobryidae), with description of new species from Hungary - Winkler, Daniel; Traser, György N. (Zootaxa, 2012)
The Lepidocyrtus pallidus-serbicus group has been created for the two eponymic species only, but at the present time thegroup is composed by a total of 6 species: L. pallidus Reuter, 1890; L. serbicus Denis, 1933; L. pseudosinelloides Gisin,1967; L. weidneri Hüther, 1971; L. arrabonicus Traser 2000 and L. tomosvaryi sp. nov. The main characteristic shared byevery species in this group is the dorsal body macrochaetotaxy: 00/0101+2 and the presence of M 1 M 2 on the labial triangle.The new species is close to L. serbicus but clearly differs from it in the presence of a small dental tubercle at the basal part of the dens on the dorsal surface. An identification key is given for differentiating all species of this group.